KARANJ (PONGAMIA PINNATA) – AN AYURVEDIC AND MODERN OVERVIEW: KARANJ (PONGAMIA PINNATA) - THAKUR, SHIFALI; KAURAV, HEMLATA; CHAUDHARY, GITIKA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Pongamia pinnata is one of the significant herbal plants with different therapeutic medicinal properties. P. pinnata is a potential medium-sized legume tree, also known as Karanja. It is widely distributed in Indian Western Ghats. This plant is mostly cultivated around coastal areas, riverbanks, tidal forests, and roadsides. Conventionally, the leaves, seeds, and the whole plant were utilized in the treatment of many ailments. There are various phytochemicals isolated from the P. pinnata plant. Karanjin is the principal furanoflavonoid of the plant. It was known to be the first crystalline compound isolated from this plant. The plant is therapeutically important in traditional medicine as well as in modern drugs. Oil extract from the P. pinnata seeds is utilized in agriculture and pharmacy. Seed oil is also proved to be a biofuel in recent studies. There are various therapeutical uses of the P. pinnata, including antiulcer, anti-diarrheal, antiplasmodial, anti-inflammatory, anti-viral, anti-bacterial, anti-lice, and others. The karanja seeds contain 27-40%(w/w/) oil. Commercially, the seed oil of the P. pinnata is used as biodiesel. The present review article reveals the overall ayurvedic and modern therapeutic information of P. pinnata with various reported ayurvedic literature and scientific pharmacological studies.